The Evaluation of Anemia Among Stunted Children Aged 6–24 Months in Bandung District, West Java, Indonesia - Susanah, Susi; Marcelius, David; Rakhmilla, Lulu Eva; Rossanti, Rini; Febrianti, Sindy Amalia; Sakinah, Siti; Winyarti, Winyarti; Lutfia, Safira Satyani; Judistiani, Raden Tina Dewi; Gurnida, Dida Akhmad; Setiabudiawan, Budi (Children (Basel), 2025)
Background/Objectives: Anemia, particularly iron-deficiency anemia (IDA), and stunting remain notable early childhood public health challenges in Indonesia; however, studies are still scarce. This study aimed to determine the co-occurrence of anemia and stunting (CAS), their prevalence, and the associated factors, as well as to describe the erythrocyte parameters. Methods: Approximately 2200 children aged 6–24 months were identified by midwives to have problematic nutritional status at Bandung Regency, West Java, Indonesia. These children were included in the population frame for a cohort study of vitamin D deficiency, vitamin D binding protein, and its impact on neurodevelopmental functions. A cross-sectional study was nested in the cohort study. The subjects were selected by stratified random sampling of 270 villages to meet the required number of samples. Medical doctors reassessed the anthropometric measurements and performed guided interviews to collect associated factors for IDA and CAS. Erythrocyte profiles of the children were examined from venous blood. Results: One hundred and ninety-four subjects were included in the analysis, among which 54.1% were stunted. Anemia was present in 40.7% of the subjects, largely due to IDA (87.3%). A wasting child and the factor of low paternal education (up to elementary school) were associated with IDA (aOR of 7.12 and aOR of 3.32, p < 0.05, respectively). Co-occurrence of anemia and stunting was found in 41/194 (21.1%) subjects, but it did not show significant association. Conclusions: Anemia and stunting were prevalent among children aged 6–24 months, but no associations were found between anemia and stunting in this study. Iron deficiency was the main cause of anemia, and it was associated with wasting and low paternal education.